Does Clear Aligner Treatment Result in Different Patient Perceptions of Treatment Process and Outcomes Compared to Conventional/Traditional Fixed Appliance Treatment: A Literature Review - Ben Gassem, Afnan A. (European Journal of Dentistry, 2021)
This study sought to systematically review the literature to determine whether clear aligner treatment results in different patient perceptions of treatment process and outcomes compared with conventional fixed appliance treatment. A systematic review was conducted to identify studies that examined differences in patient perceptions between clear aligners and conventional fixed appliance treatment. Studies were identified through searching relevant terms using PubMed and Embase. Following review of identified articles, key information about the studies including study design, setting, comparison groups, sample size/response rate, study location, primary outcomes, and statistical tests used were extracted. A total of 13 articles were identified that met the inclusion criteria for this study. These studies described a variety of outcomes which were divided into two broad categories: treatment process (pain, chewing, speech, daily routine, etc.) and treatment outcomes (satisfaction level, smile outcome perceptions, etc.). There was the strongest evidence that clear aligners had a positive impact with respect to treatment process compared with fixed orthodontic appliances. This study highlights that clear aligners may be effective for improving treatment-process-related outcomes among orthodontic patients. More studies need to be conducted to determine whether clear aligners have a beneficial impact with respect to treatment outcomes.
Keywords: clear aligners; Invisalign; treatment process; treatment outcomes